2007
DOI: 10.1124/jpet.107.121665
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Stimulation of Presynaptic Serotonin Transport by A3Adenosine Receptors

Abstract: The inactivation of synaptic serotonin (5-hydroxytryptamine, 5-HT) is largely established through the actions of the presynaptic, antidepressant-sensitive 5-HT transporter (SERT, SLC6A4). Recent studies have demonstrated post-translational regulation of SERT mediated by multiple Ser/Thr kinases, including protein kinases C and G (PKC and PKG) and p38 mitogen-activated protein kinase (MAPK), as well as the Ser/ Thr phosphatase PP2A. Less well studied are specific surface receptors that target these signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 39 publications
6
70
1
Order By: Relevance
“…Recent results obtained in transfected cells and in mouse brain synaptosomes showed that adenosine yielded an increase in SERT activity; however, in this case, the effect was mediated by A 3 adenosine receptors [38,39]. These results are in contrast to ours; nevertheless, the tissue studied, the adenosine receptor and the signalling pathway involved were different.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent results obtained in transfected cells and in mouse brain synaptosomes showed that adenosine yielded an increase in SERT activity; however, in this case, the effect was mediated by A 3 adenosine receptors [38,39]. These results are in contrast to ours; nevertheless, the tissue studied, the adenosine receptor and the signalling pathway involved were different.…”
Section: Discussioncontrasting
confidence: 99%
“…PKA, PKC and PKG activation have also been demonstrated to impose post-translational regulation on SERT by phosphorylation, possibly reflecting the heterologous context of SERT expression. Zhu et al have reported that involvement of A3AR in serotonin transporter trafficking and activation in RBL-2H3 cells and SERT stimulation by A3AR requires activation of PKG by a phospholipase C, Ca 2+ , NOS and cGMP-dependent mechanism (14,27). In the present study, we provided evidence that Ca 2+ -CaMK-II/iNOS/PKG-I signaling pathways contribute to up-regulation of SERT in RBL-2H3 cells by LPS.…”
Section: Discussionsupporting
confidence: 71%
“…Many studies have demonstrated RBL-2H3 cells expressing serotonin synthesis and transporter systems as an ideal model for elucidating the regulatory mechanisms relating to SERT (14)(15)(16). Consistent with previous reports, results obtained in our laboratory have shown that the fluorescent styryl dye ASP assay enables the detection of dynamic transport activities of SERT and is amenable for measuring 5-HT uptake (17)(18)(19)(20)(21).The results obtained from the present study showed that LPS treatment enhances 5-HT uptake in RBL-2H3 cells in a dosedependent manner.…”
Section: This Study Is Aimed To Investigate the Underlying Mechanism mentioning
confidence: 99%
“…Synaptosomes were prepared as described previously (52) with 5-HT transport activity assessed at 37°C as previously described (53). For competition uptake assays, samples containing 25 to 100 μg were incubated in duplicate with 20 nM Electrophysiologic Slice Preparation and Recordings.…”
Section: Methodsmentioning
confidence: 99%